Synthesis of organic photothermal agents for combined photothermal/enzymatic dynamic therapy of breast cancer - Zhang, Meifeng; Huang, Qian; Zhang, Bo; Wu, Wei (Frontiers in Materials, 2023)
Nanoparticle-based photothermal therapy is an effective treatment for superficial tumors. However, due to the highly heterogeneous nature of breast cancer, photothermal therapy (PTT) used alone was unable to achieve satisfactory therapeutic results. Therefore, combining PTT with other therapies is a promising strategy for tumor treatment. Inspired by the significant elevation of lactate levels at the tumor site, we prepared a novel nanocomposite therapeutic platform (PPy-LOX) for combined PTT and enzyme-dynamic treatment (EDT) of breast cancer. In detail, Polypyrrole (PPy) nanoparticles were synthesized using a simple chemical oxygenation method and polyvinylpyrrolidone (PVP) was used as a surface linker to enhance its colloidal stability. Further, the loading of lactate oxidase (LOX) is accomplished by simple physical mixing. The in vivo and in vitro results demonstrated the excellent biocompatibility of the synthesized PPy-LOX NPs. More importantly, PPy-LOX NPs has excellent photothermal conversion (η=29.9%) and lactic acid catalytic ability. On the one hand, the temperature increase induced by near-infrared light irradiation can cause apoptosis of tumor cells; on the other hand, LOX can catalyze the generation of hydrogen peroxide from excess lactate in the tumor microenvironment to induce oxidative stress to kill tumor cells. In conclusion, the combination of PTT and EDT can effectively kill tumor cells. This work provides new ideas on how to design rational nanotherapeutic systems by exploiting the tumor microenvironment.